Effects of Different Bleaching Methods on the Enamel Mineralization Level - Sürmelioğlu, Derya (European Journal of Therapeutics, 2023)
Objective: The aim of the present study is to evaluate the mineralization level of human enamel following bleaching treatment using a laser fluorescence device. Methods: A total of 45 patients were divided into three groups according to the bleaching method used. In Group 1, chemical bleaching was conducted with 35% hydrogen peroxide (HP). In Group 2, we used 35% HP activated by a 980 nm diode laser. In Group 3, bleaching was conducted with ozone. Levels of mineralization were measured using a laser fluorescence device before bleaching, just after bleaching and also on the 2-weeks and 1-month following bleaching. Results: Data were analyzed using the Kruskal–Wallis test, one-way analysis of variance, and Mann–Whitney U test. The values were significantly higher compared to initial values following bleaching and at the 2-weeks follow-up for Groups 1 and 2 (p<0.05). However, values were similar to the initial values at the 1-month recall (p>0.05). For Group 3, the values were significantly reduced following bleaching (p<0.05), while the values of each postbleaching were statistically similar (p>0.05). Conclusion: Both chemical and laser-activated bleaching resulted in a significant reduction of the mineralization level, while bleaching with ozone did not. Bleaching with ozone seems to be safer in terms of demineralization compared to HP.